2023
DOI: 10.1002/jat.4504
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, alcohol, and phosphate toxicity

Abstract: Alcohol consumption is associated with an increased risk of breast cancer, even at low alcohol intake levels, but public awareness of the breast cancer risk associated with alcohol intake is low. Furthermore, the causative mechanisms underlying alcohol's association with breast cancer are unknown. The present theoretical paper uses a modified grounded theory method to review the research literature and propose that alcohol's association with breast cancer is mediated by phosphate toxicity, the accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…In 2023, the present authors published a review proposing that the association of alcohol consumption with increased risk of breast cancer is mediated by hyperphosphatemia caused by alcohol-induced rhabdomyolysis which releases intracellular phosphate from skeletal muscle into the serum [35]. Also in 2023, the authors found that a 2.30 relative risk for breast cancer incidence in a cohort of middle-aged U.S. women was associated with >1800 mg dietary phosphorus compared to 800-1000 mg phosphorous recommended by the U.S. National Kidney Foundation for patients with CKD (RR: 2.30; 95% CI: 0.94-5.61; p = 0.07) [36].…”
Section: Diet and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In 2023, the present authors published a review proposing that the association of alcohol consumption with increased risk of breast cancer is mediated by hyperphosphatemia caused by alcohol-induced rhabdomyolysis which releases intracellular phosphate from skeletal muscle into the serum [35]. Also in 2023, the authors found that a 2.30 relative risk for breast cancer incidence in a cohort of middle-aged U.S. women was associated with >1800 mg dietary phosphorus compared to 800-1000 mg phosphorous recommended by the U.S. National Kidney Foundation for patients with CKD (RR: 2.30; 95% CI: 0.94-5.61; p = 0.07) [36].…”
Section: Diet and Cancermentioning
confidence: 99%
“…"Limit alcohol consumption-For cancer prevention, it's best not to drink alcohol" Non-traumatic rhabdomyolysis from alcohol intake increases serum Pi [35].…”
Section: Wcrf/aicr Recommendations For Cancer Prevention Additional A...mentioning
confidence: 99%
See 1 more Smart Citation
“… High dietary phosphate and cancer-cell signaling [ 96 ]. This flowchart shows that high dietary phosphate activates the phosphoinositide 3-kinase (PI3K)/Akt/mTOR signaling pathway while deactivating tumor suppression by PTEN and CTMP, increasing cell growth in tumorigenesis.…”
Section: Figurementioning
confidence: 99%
“…Breast cancer exhibits diversity at the biological level, with prognosis being impacted by a range of factors such as molecular subtypes, age at diagnosis, and histopathological features ( Brown et al, 2023 ). Recent advancements in early detection methods for breast cancer and the ongoing progress in treatment options have greatly enhanced the outlook for patients with this disease ( Will et al, 2023 ; Brown et al, 2024 ). Especially as people’s understanding of the immune microenvironment deepens, the utility of immunotherapy in breast cancer treatment continues to ascend.…”
Section: Introductionmentioning
confidence: 99%